2017
DOI: 10.1080/16506073.2017.1366546
|View full text |Cite
|
Sign up to set email alerts
|

Adherence predictors in an Internet-based Intervention program for depression

Abstract: Internet-delivered psychotherapy has been demonstrated to be effective in the treatment of depression. Nevertheless, the study of the adherence in this type of the treatment reported divergent results. The main objective of this study is to analyze predictors of adherence in a primary care Internet-based intervention for depression in Spain. A multi-center, three arm, parallel, randomized controlled trial was conducted with 194 depressive patients, who were allocated in self-guided or supported-guided interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
16
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 47 publications
6
16
2
Order By: Relevance
“…Many of these programmes utilise cognitive-behavioural therapy strategies and are delivered in a structured format, grouping topics into approximately five or six modules designed to be accessed sequentially or to be explored freely as a user needs. 9 Frequency of logins, time spent online, number of modules or activities completed, 23 data entered, minimum number of modules required 20 as well as pages accessed and printed are common ways to measure adherence. 19,24,25 While these data may be collected, they are often not reported.…”
Section: The Concept Of Adherence and The Impact On Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Many of these programmes utilise cognitive-behavioural therapy strategies and are delivered in a structured format, grouping topics into approximately five or six modules designed to be accessed sequentially or to be explored freely as a user needs. 9 Frequency of logins, time spent online, number of modules or activities completed, 23 data entered, minimum number of modules required 20 as well as pages accessed and printed are common ways to measure adherence. 19,24,25 While these data may be collected, they are often not reported.…”
Section: The Concept Of Adherence and The Impact On Outcomesmentioning
confidence: 99%
“…25 Importantly, this would help determine whether early treatment improvements do influence further programme usage. 20 Currently, research on the effects of alliance on adherence in e-mental health programmes is scarce. 70,71 However, one study demonstrated a positive relationship between perceived emotional connection with the programme (myCompass) and number of logins, psychoeducation modules completed and frequency of self-monitoring.…”
Section: Further Evaluationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large body of research has focused on the study of adherence predictors in the past years [21,[24][25][26][27][28][29][30][31]. Nevertheless, the results are contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…[ 31 ] There is evidence that psychotherapy delivered by telephone or online may be useful for patients with depression, but less information is available regarding the use of Internet-based programs that focus on lifestyle in health emergency situations in which people are required to restrict their mobility and maintain physical distance. [ 32 , 33 ] As far as we are aware, no previous studies have examined the effect of this approach for patients with TRD.…”
Section: Introductionmentioning
confidence: 99%